2020
DOI: 10.3390/ijms21186743
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Evogliptin on Steatohepatitis in High-Fat-Fed Mice

Abstract: There are few studies on the effects of dipeptidyl peptidase-4 inhibitors on steatohepatitis. We explored whether evogliptin (Evo), a dipeptidyl peptidase-4 inhibitor, protects against steatohepatitis in a high-fat diet (HFD)-fed mice and whether these effects involve modulation of mitophagy. Adult male C57BL/J mice were divided into the normal diet (ND), HFD (45% of energy from fat) with Evo (250 mg/kg) (HFD + Evo), and HFD groups at 4 weeks of age and were sacrificed at 20 weeks of age. The HFD group showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
1
1
Order By: Relevance
“…We found that EVO treatment reduced blood glucose and HbA1c levels and improved glucose tolerance in db/db mice, consistent with the results of other studies [37][38][39] . However, in our study, EVO did not influence body weight gain, which differs from previous publications that reported that EVO decreased 20 or increased body weight 40 . This difference may be due to the distinct research subjects, the age of the mice, or the dose of EVO.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We found that EVO treatment reduced blood glucose and HbA1c levels and improved glucose tolerance in db/db mice, consistent with the results of other studies [37][38][39] . However, in our study, EVO did not influence body weight gain, which differs from previous publications that reported that EVO decreased 20 or increased body weight 40 . This difference may be due to the distinct research subjects, the age of the mice, or the dose of EVO.…”
Section: Discussioncontrasting
confidence: 99%
“…Evogliptin® (EVO), a novel DPP-4 inhibitor, was developed by Dong-A, Republic of Korea, and approved as an oral antihyperglycemic drug for the treatment of T2DM by the Ministry of Food and Drug Safety of Korea in 2015. EVO has an effect on gluconeogenesis, hepatic steatosis, vascular inflammation, and whole-body composition [20][21][22][23] . However, the effect of DPP-4 inhibitors on HF is still unknown, and studies on EVO to understand its impact on diabetes and its complications, including DCM, are lacking.…”
Section: Introductionmentioning
confidence: 99%